BALI PIG FARMING BUSINESS MARKETING STRATEGY ON CRITICAL LAND (Case Study in Karangasem Regency, Bali Province) - W.Y.N.W., Putra; Putri, B.R.T.; Sumardani, N. L.G. (Jurnal Peternakan Tropika, 2023)
This study aims to analyze the internal and external environmental factors of bali pig farming business on critical land in Karangasem Regency that affect the marketing of Bali pig herds, determine the position of Bali pig farming business on critical land in Karangasem Regency in the industry and formulate the right marketing strategy for Bali pig farming business. This study is a case study conducted in Karangasem Regency. The number of breeder respondents was 30 people, and the expert respondents were 3 people. The data sources used are primary and secondary data. The data was collected through observation , indepth interviews and interviews with the help of questionnaires. The analysis used there are 3 namely, 1) internal and external analysis of efforts to find factors of strengths, weaknesses, opportunities and threats to be included in the IFE and EFE matrices; 2) the IE matrix used to determine the position of the business; 3) SWOT analysis is used to devise alternative marketing strategies for Balinese pig farming businesses. The results of ife and EFE analysis of efforts obtained by    Bali    pigs     are    resistant     to    sufficiency     (low     quality     feed and extreme environment) (major strength), farmers only focus on maintenance, while the marketing management and health management sectors are less noticed (the main weakness), the high demand for bali pigs for rolled pigs (major opportunities) and the entry of purebred pigs into all walks of life in Bali to determine the role of Balinese pigs as meat producers (the main threat). This study shows that the position of bali pig farming business on critical land is in cell V (maintain and maintain) in the IE matrix with an IFE value of 2.93 and an EFE value of 2.52. Keywords : marketing strategy, IE, SWOT, bali pig